2020
DOI: 10.3390/coatings10020090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanostructured Chitosan/Propolis Coatings on the Quality and Antioxidant Capacity of Strawberries During Storage

Abstract: Strawberries have a thin epidermis and a high respiration rate. The use of edible coatings containing chitosan nanoparticles (CSNPs) and propolis (P) has been effective in preserving the shelf life and antioxidant capacity of various fruit and vegetable products. The present research evaluated the effect of coatings with CSNPs and P on the quality, antioxidant compounds, and antioxidant capacity of strawberries. The specific coatings that were evaluated were chitosan (CS), CS+CSNPs33%, CS + CSNPs + P10%, CS + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 35 publications
5
31
1
5
Order By: Relevance
“…This effect is intensified when BSLN are incorporated. Hussain et al (2012) [29], reported weight losses between 3% and 7% after 12 days of storage in strawberries coated with different concentrations of CMC also treated with gamma radiation; while in our study the results were achieved without additional treatment and Martínez-González et al (2020) [30], achieved a control of weight loss over 8 days when employing nanoparticles of chitosan and propolis with a weight loss of 9.7%, which shows that possible to agree that the use of a small proportion of BSLN (10 g/L) was more effective. Changes in pH, SSC, and acidity are associated with weight loss in all systems.…”
Section: Firmness and Decay Indexcontrasting
confidence: 41%
“…This effect is intensified when BSLN are incorporated. Hussain et al (2012) [29], reported weight losses between 3% and 7% after 12 days of storage in strawberries coated with different concentrations of CMC also treated with gamma radiation; while in our study the results were achieved without additional treatment and Martínez-González et al (2020) [30], achieved a control of weight loss over 8 days when employing nanoparticles of chitosan and propolis with a weight loss of 9.7%, which shows that possible to agree that the use of a small proportion of BSLN (10 g/L) was more effective. Changes in pH, SSC, and acidity are associated with weight loss in all systems.…”
Section: Firmness and Decay Indexcontrasting
confidence: 41%
“…Total phenolic contents (TPC) (Folin-Ciocalteu reagent) data are expressed in equivalents of mg of gallic acid for 100 g of film (mg GAE/100 g film) [78,[118][119][120]155,156,[215][216][217][218][219][220][221][222][223][224][225][226][227][228].…”
Section: Antioxidant and Antimicrobial Activitymentioning
confidence: 99%
“…Total flavonoids (aluminum chloride reagent) data are expressed in mg of quercetin equivalents for 100 g of film (mg QE/100 g film) [46,140,163,188,216,217,[229][230][231][232][233] • DPPH method (1,1-diphenyl-2-picrylhydrazyl radical reagent-DPPH) data are expressed in mg of ascorbic acid equivalents for 100 g of film (AAE/100 g of film) [30,32,37,47,72,160,162,163,169,199,[233][234][235][236][237][238][239] • ABTS (2,20-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid reagent-ABTS) data are expressed in mg of ascorbic acid equivalents for 100 g of film (AAE/100 g of film) [32,47,166,174,211,235,239,240] Antibacterial activity is performed by the assessment of the zone of inhibition assay on a solid medium placed in Petri dishes and containing specific media for each microorganism tested [74,125,129,141,171,176,179,…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gelatinbased edible coatings by propolis were tested, and the active films showed a high antifungal activity against the tested fungus [63]. It was also noted that the incorporation of propolis with chitosan provides higher antimicrobial activity [64,65]. In one of these studies, Correa-Pacheco et al [64] noted that the propolis-containing formulations (10%, 20%, and 30%) had a strong inhibitory effect on Listeria monocytogenes and 10% formulation had a similar effect on Escherichia coli and provided better preservation of strawberries.…”
Section: Antimicrobial and Fungicidal Effectsmentioning
confidence: 99%